Sustainable development and management of a crucial natural resource : A research protocol to model groundwater flow in Nalanda District, Bihar, India - Mizan, Syed Adil; Sikka, Alok; Urfels, Anton; Laing, Alison M.; Krupnik, Timothy J. (TAFSSA, 2023)
Across South Asia, millions of small-scale farmers are confronted with a range of urgent challenges. These include poverty, malnutrition, environmental deterioration, and the growing impacts of climate change and unpredictability (Ericksen et al., 2011). Despite these pressing concerns, the region’s farming systems still have potential to sustainably its productivity and profitability (Islam et al., 2019; Gathala et al., 2021). The Transforming Agrifood Systems in South Asia (TAFSSA) research integrates interdisciplinary studies at both the farm and landscape levels to discover approaches that enable farmers to enhance their income and nutritional output while also preserving natural resources.